UTILIZATION PATTERN OF RESIDENTIAL TERRACE AS A TRADING PLACE IN KAMPUNG TRIDI JODIPAN MALANG - Adita Ronarizkia; Yusfan Adeputera Yusran (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2019)
Kampung Tridi, Jodipan Malang, which was initially a slum residential area has transformed now into a colorful area with a concept of colorful order, arranged linearly according to the houses pattern. This setting is positively effective to attract tourist interest to come and success in changing the aspect of social, culture and economy of the residents. The aspect which has been through adequate significant change is the economy, which is indicated from the number of residents who take benefit from their house's terrace that initially used as a conventional family area, now turn into an area of trading. This change is conducted to be economic support in order to fulfill their life needs. This research aims to identify the pattern of terrace utilization as the place where the trading activity takes place in Kampung Tridi Jodipan Malang. This research exerts the method of descriptive qualitative which identifies the pattern of terrace utilization through field survey, interview, and literature studies, while the method of analysis used behavior mapping. This research finding shows that the utilization pattern of the residential terrace as the trading spot is located exactly in the front part of the house, that is the terrace. The houses that using the terrace as the trading spot are mostly located in the front of the main path which leads to the Jembatan Kaca (Glass bridge) that connects Kampung Tridi with Kampung Warna-warni in the south.